Characterization of the binding site(s) of heart muscle chalone - Groenewald, Elsa S (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ms.Sc. Med. Sci.(Medical Biochemistry)) - University of Stellenbosch, 1983.